Labour force participation and the growth of women's employment, Ireland 1971-1991 - Walsh, Brendan M. (Economic & Social Studies, 1993)
This paper studies changes in labour force participation rates and in the structure of the Irish labour force over the period 1971-1991. The rise in participation rates among females aged 25-54 and the decline among older and younger people of both sexes altered the demographic structure of the labour force significantly. The reasons for these changes are explored using time series of annual participation rates. I t is shown that participation rates among those aged 15-24 and males aged 65 and over, although dominated by exogenous negative trends, are also responsive to the returns to labour force participation which in turn depend on wage rates, unemployment benefits and the rate of unemployment. Participation rates among women aged 20-54 are responsive to the returns to entering the labour force and the sharp fall in the birth rate during the 1980s, argued here to be largely exogenous. The marked decline in labour force participation among males aged 55-64 is difficult to explain with the available data. The effect of increases in women's labour supply on the rate of unemployment is discussed.
Keywords: Labour force; Female employment; Ireland